CONDITIONS OF IMPLEMENTATION EFFECTIVE CONTRACT FOR EDUCATIONAL RESEARCH STAFF OF UNIVERSITIES - A. A. Kondrateva; I. M. Shirko (Модернизация, инновация, развитие, 2015)
Increasing salaries educational research staff in relation to the average salary in the subject of the Russian Federation will directly depend on the effectiveness of their work and the quality of their services. Salary increase educational research staff must be linked to the mechanism of the transition to the «effective contract». The special features of the introduction of «effective contract» refers most complete reflection of the complexity of the employment agreements of labor between workers based on indicators and criteria to evaluate working conditions of pay and benefits.